Prioritising outcomes for evaluating eosinophil-guided corticosteroid therapy among patients with acute COPD exacerbations requiring hospitalisation: a Delphi consensus study - Romain Kessler; Alain Didier; Mathieu Molimard; A Bourdin; Thierry Chinet; Chantal Raherison; Nicolas Roche; Carey Meredith Suehs; Cécile Chenivesse; Pierre-Régis Burgel; F Couturaud; Gaëtan Deslee; et al. (BMJ Open)
Objectives Presently, those outcomes that should be prioritised for chronic obstructive pulmonary disease (COPD) exacerbation studies remain unclear. In order to coordinate multicentre studies on eosinophilia-driven corticosteroid therapy for patients hospitalised for acute exacerbation of COPD (AECOPD), we aimed to find consensus among experts in the domain regarding the prioritisation of outcomes.Design A modified Delphi study was proposed to recognised COPD experts. Two brainstorming questionnaires were used to collect potential outcomes. Four subsequent rounds of questionnaires were used to rank items according to a six-point Likert scale for their importance in the protocol, as well as for being the primary outcome. Priority outcome criteria were predefined as those for which ≥70% of experts indicated that the outcome was essential for interpreting study results.Setting COPD exacerbation management in France.Participants 34 experts recommended by the French Language Pulmonology Society were invited to participate. Of the latter, 21 experts participated in brainstorming, and 19 participated in all four ranking rounds.Results 105 outcomes were ranked. Two achieved consensus as candidate primary outcomes: (1) treatment failure defined as death from any cause or the need for intubation and mechanical ventilation, readmission because of COPD or intensification of pharmacologic therapy, and (2) the time required to meet predefined discharge criteria. The 10 secondary priority outcomes included survival, time with no sign of improvement, episodes of hospitalisation, exacerbation, pneumonia, mechanical or non-invasive ventilation and oxygen use, as well as comorbidities during the initial hospitalisation.Conclusions This Delphi consensus project generated and prioritised a great many outcomes, documenting current expert views concerning a diversity of COPD endpoints. Among the latter, 12 reached consensus as priority outcomes for evaluating the efficacy of eosinophil-driven corticosteroid therapy in AECOPD inpatients.Study registration The eo-Delphi project/protocol was registered on 23 January 2018 at https://osf.io/4ahqw/.